Response to Different Oxygen Partial Pressures and Evolution Analysis of Apoptosis-Related Genes in Plateau Zokor (Myospalax baileyi) - An, Zhifang; Chen, Xiaoqi; Li, Jimei (Frontiers in Genetics, 2022)
The plateau zokor (Myospalax baileyi) is a native species of the Qinghai–Tibet Plateau that spends its entire life underground in sealed burrows with hypoxic conditions. The present study aimed to assess the sequence characteristics of apoptosis-related genes and the response to different oxygen partial pressures (pO2) in plateau zokor and Sprague-Dawley rats. The sequences of the p53-induced protein with a death domain (Pidd), p53-upregulated modulator of apoptosis (Puma), insulin-like growth factor binding protein 3 (Igfbp3), and apoptosis protease-activating factor 1 (Apaf1) were evaluated concerning homology and convergent evolution sites, and their mRNA levels were evaluated in different tissues under 14.13 (3,300 m) and 16.12 kPa (2,260 m) pO2 conditions. Our results showed that, (1) the sequences of the apoptosis-related genes in plateau zokor were highly similar to those of Nannospalax galili, followed by Rattus norvegicus; (2). Pidd, Puma, Igfbp3, and Apaf1 of plateau zokor were found to have five, one, two, and five convergent sites in functional domains with N. galili, respectively. Lastly (3), under low pO2, the expression of Pidd and Puma was downregulated in the lung of plateau zokors. In turn, Igfbp3 and Apaf1 were upregulated in the liver and lung, and Puma was upregulated in the skeletal muscle of plateau zokor under low pO2. In Sprague-Dawley rats, low pO2 downregulated Puma and Apaf1 expression in the liver and downregulated Igfbp3 and Puma in the lung and skeletal muscle separately. In contrast, low pO2 upregulated Pidd expression in the liver and skeletal muscle of Sprague-Dawley rats. Overall, the expression patterns of Apaf1, Igfbp3, and Puma showed the opposite pattern in the liver, lung, and skeletal muscle, respectively, of plateau zokor as compared with Sprague-Dawley rats. In conclusion, for the long-time adaptation to hypoxic environments, Pidd, Puma, Igfbp3, and Apaf1 of plateau zokor underwent convergent evolution, which we believe may have led to upregulation of their levels under low oxygen partial pressures to induce apoptosis, so as to suppress tumorigenesis under hypoxic environments in plateau zokor.